Exploring the views of academics on an academic leadership program in higher education - Frantz, J.; Marais, J.; Du Plessis, M. (South African Journal of Higher Education, 2022)
Leadership in higher education institutions has been receiving growing interest, because of the role institutions play in developing students to become leaders in the broader society. However, institutions have to equip staff, adequately, with leadership skills, first, and one way of doing this, is through a leadership development programme for academic staff. The purpose of this current study was to explore and describe the impact of an academic leadership development programme, based on the perceptions of the participants. In this study, a qualitative, exploratory descriptive, research design was employed. Thirteen (13) participants were purposively selected to participate in the study. Data were collected using individual, open-ended, face-to-face interviews. The data were transcribed, verbatim, and analysed, using thematic analysis. Four key themes emerged: (1) emotional responses to the programme; (2) professional application of skills; (3) benefits from the programme; and (4) recommendations. The programme had an impact on both the personal and professional lives of the participants, which is evidence of the truly transformative nature of the programme. The study, however, is limited because the researchers only sought to explore the perceived impact of a leadership development programme. To determine the true impact, it would need to be studied, using multiple sources.